European Territorial Cooperation : theoretical and empirical approaches to the process and impacts of cross-border and transnational cooperation in Europe /: theoretical and empirical approaches to the process and impacts of cross-border and transnational cooperation in Europe. (2018) - Unknown
No abstract available